PENGGUNAAN BAHASA INGGRIS SECARA MAKSIMAL UNTUK MENYONGSONG MASYARAKAT EKONOMI ASEAN (MEA) 2025 - Sarah Nasution (Universitas Dharmawangsa, 2018)
This study aims to determine the extent to which the community as citizens of Indonesia understandthe entry of the globalization with the marked by the ASEAN Economic Community (MEA) requiredthe Mastery of International Language used is English. In this research, writer use library researchmethod or literature study with the result of research is still lack awareness and readiness of societyas citizen that information system so fast enter Indonesia so that we as society always step belowMalaysia, Brunei, Singapore and now Taiwan. As an Asean Member of Indonesia should furtheroptimize its human resources to be able to compete in this MEA Era. Because in any field, the use ofEnglish will always be used as a valid communication tool, which is used in daily life later.